Phytoremediation Potentiality of Bottle Gourd Plant (Lagenaria siceraria) (Journal of Biodiversity Conservation and Bioresource Management, 2024)
A pot experiment of bottle gourd plant with Pb, Zn, NPK and Vermicompost (VC) was carried out at the Department of Soil, Water and Environment, University of Dhaka. The aim of the study was to introduce a phytoremedial technique. The bottle gourd (Lagenaria siceraria) plant was used in the trial for evaluating its potentiality to accumulate Pb and Zn from soil and translocate these elements to different parts of the plant. Twelve treatments (T) were utilized in the experiment including control (T1). The remaining treatment groups were composed of different ratios of VC and recommended dose of NPK- with and without lead and Zinc. Tolerance to metal stress by the bottle gourd plant was evident in terms of higher biomass and yield production with the Pb and Zn. The maximum total biomass (leaf + stem + root) of fresh (67.49 g) and dry yield (8.41g) was achieved with Pb addition to T11. Bioconcentration factor (BCF) and Translocation Factor (TF) greater than one (BCF>1 and TF>1) were considered indicators of heavy metal accumulators and translocators, respectively. Among the Pb treatments, highest BCF achieved in leaf (1.67) with T12, in stem (1.82) with T8, in root (4.67) with T11 and maximum TF (2.87) found   with T11.  The Zn treatments exerted the highest BCF value in leaf (1.80), and in stem (1.64) with T10, in root (2.70) with T12, lowest value of BCF and TF were displayed in control (T1). Research exposed that bottle gourd plants had transferred both the heavy metals from soil significantly. The highest Pb accumulation in leaf was found to be 0.0023% (dry weight) in T10 and the lowest (0%) in T1. The highest translocation factor was found in T5 for Pb and in T11 for Zn. Moreover, bioconcentration factor (Pb) in shoots exhibited a significant, strong, and negative correlation (r = -0.804, p = 0.002) with the soil organic carbon content. There was also a strong, significantly negative correlation between total Pb content in soil and BCF (leaf) (r = -0.717, p = 0.009), as well as BCF (stem) (r = -0.692, p = 0.013). Similar relationship was found in case of Zn. The study revealed that bottle gourd plants possess phytoremedial potentiality which will be beneficial for the pollution context of Bangladesh. Further investigation is needed for greater research interest.Biodivers. Conserv. Bioresour. Manag. 2024, 10(1): 59-74